2013
DOI: 10.4174/jkss.2013.84.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for parastomal hernia: based on radiological definition

Abstract: PurposeThe aim of this study was to investigate the clinical and radiological incidence of parastomal hernia and to analyze the risk factors for parastomal hernia.MethodsWe reviewed retrospectively 108 patients with end colostomy from January 2003 to June 2010. Age, sex, surgical procedure type, body mass index (kg/m2), stoma size, and respiratory comorbidity were documented.RESULTSThere were 61 males (56.5%) and 47 females (43.5%). During an overall median follow-up of 25 months (range, 6 to 73 months), 36 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 17 publications
3
44
0
1
Order By: Relevance
“…While malnutrition has been reported previously as a risk factor for PH development 24 , this is the first report to our knowledge to identify a quantifiable variable, preoperative albumin level, that is significantly associated with PH development.. Like other investigators analyzing factors associated with hernia formation, we found female gender was significantly associated with PH development. 25,26 Similar to Klein and colleagues, we did not find an association between the type of stoma (end-versus Turnbull loop stoma) and the risk of developing a PH after ileal conduit. 27 Since all Turnbull stomas in this series were performed by a single surgeon (BHB), this analysis may be impacted by surgeon technique rather than by the type of diversion performed and is a limitation in this study.…”
Section: Discussionsupporting
confidence: 65%
“…While malnutrition has been reported previously as a risk factor for PH development 24 , this is the first report to our knowledge to identify a quantifiable variable, preoperative albumin level, that is significantly associated with PH development.. Like other investigators analyzing factors associated with hernia formation, we found female gender was significantly associated with PH development. 25,26 Similar to Klein and colleagues, we did not find an association between the type of stoma (end-versus Turnbull loop stoma) and the risk of developing a PH after ileal conduit. 27 Since all Turnbull stomas in this series were performed by a single surgeon (BHB), this analysis may be impacted by surgeon technique rather than by the type of diversion performed and is a limitation in this study.…”
Section: Discussionsupporting
confidence: 65%
“…Other factors in the literature that have been suggested but not validated include malnutrition, smoking status, chronic coughing, chronic constipation, ascites, corticosteroid use, and postoperative wound sepsis [21]. Technical aspects related to ostomy creation that have been suggested as risk factors for PSH include bringing the stoma out through the resection site [9], an intraperitoneal route as opposed to an extraperitoneal one [7,31,32,33], a laparoscopic approach [31], and increased aperture size [10,29,34]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…Individual patient characteristics that have been shown to be independent risk factors for PSH development include older age [7,10,28,29], increased BMI [8,30,31], increased waist circumference [30], respiratory comorbidity [8], cancer [8], diabetes mellitus [8], and the presence of other abdominal wall hernias [7]. Other factors in the literature that have been suggested but not validated include malnutrition, smoking status, chronic coughing, chronic constipation, ascites, corticosteroid use, and postoperative wound sepsis [21].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Female sex has also been shown to increase the risk of PH development [22,23]. Conceivably, stoma aperture size, if created too large, can lead to PH formation [20,23]. Comorbidities including obesity, chronic obstructive pulmonary disease, hypertension, and ascites were independent risk factors for PH development [12,22].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Increasing patient age, with some studies citing age > 60 years, is also a risk factor [18][19][20][21][22][23]. Female sex has also been shown to increase the risk of PH development [22,23]. Conceivably, stoma aperture size, if created too large, can lead to PH formation [20,23].…”
Section: Risk Factorsmentioning
confidence: 99%